Use of agricultural soils as a source of nitrous oxide emission in selected communes of Poland - Wiśniewski, Paweł; Kistowski, Mariusz (Bulletin of Geography. Physical Geography Series, 2017)
Nitrous oxide (N2O) is one of the main greenhouse gases with a potential to produce greenhouse effect nearly 300 times greater than the potential of carbon dioxide (CO2). Almost 80% of the annual emissions of this gas in Poland come from agriculture, and its main source is the use of agricultural soils. The study attempted to estimate the N2O emission from agricultural soils and to indicate its share in the total greenhouse gas emissions in 48 Polish communes. A simplified solution has been proposed for this purpose, which can be successfully applied by local government areas in order to assess the nitrous oxide emissions as well as monitor the impact of the undertaken actions on its limitation. The estimated emission was compared with the results of the baseline greenhouse gas inventory prepared for the needs of the low-carbon economy plans adopted by the studied self-governments. This allowed us to determine the share of N2O emissions from agricultural soils in the total greenhouse gas emissions of the studied communes. The annual N2O emissions from agricultural soils in the studied communes range from 1.21 Mg N2O-N to 93.28 Mg N2O-N, and the cultivation of organic soils is its main source. The use of mineral and natural fertilizers as well as indirect emissions from nitrogen leaching into groundwater and surface waters are also significant. The obtained results confirm the need to include greenhouse gas emissions from the use of agricultural soils and other agricultural sources in low-carbon economy plans.